Treatment performance and microbial community under ammonium sulphate wastewater in a sulphate reducing ammonium oxidation process. Issue 19 (24th August 2021) - Zhang, Dandan; Cui, Li; Zhu, Hao; Madani, Rayan M A; Liang, Jiyan
ABSTRACT: A laboratory testing of simultaneous removal of ammonium and sulphate was studied from the sulphate reducing ammonium oxidation (SRAO) process in a circulating flow completely anaerobic bioreactor. Three different stages of starting SRAO process were studied, and final batch tests analysis of SRAO process was conducted. During the SRAO process, the influent concentrations of NH4 + -N and SO4 2– were controlled to be 80–180 and 300–969 mg L −1 respectively. The highest removal efficiencies of NH4 + -N and SO4 2– -S were up to 94.80% and 52.57%. N/S [n(NH4 + -N)/n(SO4 2– -S)] conversion rates during the experiment had not been unified, which may be caused by the experiment's complex process. In order to further validate the biochemical interaction between ammonium and sulphate, batch tests were carried out. The extra electron acceptor, such as bicarbonate, was thought to react with ammonium by bacteria. The increase of NO3 − production and HCO3 − removal in the effluent indicated the occurrence of the new interaction between N–C. NH4 + was converted to NO2 − and NO3 − . Planctomycetes, Proteobacteria, Chloroflexi and Acidobacteria were detected in the anaerobic cycle growth reactor. The conversion of SRAO was mainly caused by the high performance of Planctomycetes . These results showed that nitrogen was converted by the partial nitrifying process, the denitrification process, and the traditional anammox process simultaneously with the SRAO process. GRAPHICAL ABSTRACT: UF0001